Differential effect of aphidicolin on adenovirus DNA synthesis and cellular DNA synthesis. - Kwant, M M (1980)
There is strong evidence for a participation of DNA polymerase gamma in the replication of adenovirus (Ad) DNA. To study a possible additional role of DNA polymerase alpha we measured the effect of aphidicolin on viral DNA replication. In intact cells, aphidicolin inhibits Ad DNA synthesis weakly. The drug concentration required for 50% inhibition of Ad DNA replication was 300-400 fold higher than for a similar effect on cellular DNA synthesis. Such a differential inhibition was also observed in AGMK cells doubly infected with SV40 and the simian adenovirus SA7. No evidence was found for modification of aphidicolin in infected cells or for a change in aphidicolin sensitivity of DNA polymerase alpha after infection. The extent of inhibition of purified DNA polymerase alpha was dependent upon the dCTP concentration. The same situation was observed when DNA synthesis was studied in isolated nuclei from uninfected cells. However, in nuclei from Ad infected cells no effect of dCTP on aphidicolin sensitivity was found. These results were taken as evidence that DNA polymerase alpha does not participate in the replication of adenovirus DNA.